2018
DOI: 10.1111/rda.13226
|View full text |Cite
|
Sign up to set email alerts
|

Early development of porcine parthenogenetic embryos and reduced expression of primed pluripotent marker genes under the effect of lysophosphatidic acid

Abstract: To further promote the early development of porcine embryos and capture "naïve" pluripotent state within blastocyst, the experiment explored the effects of lysophosphatidic acid (LPA) on the early development of porcine parthenogenetic embryos and the expression of pluripotency relevant genes. The results showed that the addition of 50 μM LPA significantly improved parthenogenetic embryo cleavage rate (82.7% vs. 74.7%, p < 0.05), blastocyst rate (24.5% vs. 11.3%, p < 0.05) and blastocyst cell count (56 ± 7.9 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Earlier studies have found that LPA treatment increases the abundance of transcripts of Connexin 43, GJC1 and CDH1, which would boost the cleavage rate and development of embryos [33]. For example, the addition of LPA into the medium can increase the cleavage rate and promote the development of mouse [34], porcine [35,36] and bovine [37,38] embryos. Consistent with these findings, our study observed that the application of LPA to the culture medium correlated with elevated cleavage and blastocyst development rates (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found that LPA treatment increases the abundance of transcripts of Connexin 43, GJC1 and CDH1, which would boost the cleavage rate and development of embryos [33]. For example, the addition of LPA into the medium can increase the cleavage rate and promote the development of mouse [34], porcine [35,36] and bovine [37,38] embryos. Consistent with these findings, our study observed that the application of LPA to the culture medium correlated with elevated cleavage and blastocyst development rates (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse embryos, similarly, LPA did not alter cleavage rates but increased the percentage of 2-cell stage embryos that developed to blastocysts [ 30 ]. In porcine parthenogenetic embryos, LPA increased the cleavage and blastocyst rates and total cell numbers [ 31 ]; all of which suggests that the function of LPA in embryos varies between different mammalian species.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse embryos, similarly, LPA did not alter cleavage rates but increased the percentage of 2-cell stage embryos that developed to blastocysts (Kobayashi et al , 1994). In porcine parthenogenetic embryos, LPA increased the cleavage and blastocyst rates and total cell numbers (Zhu et al , 2018); all of which suggests that the function of LPA in embryos varies between different mammalian species.…”
Section: Discussionmentioning
confidence: 85%